Kecemasan Matematika Siswa dan Pengaruhnya: Systematic Literature Review - Aan Putra; Yessi Yulanda (Didaktika : Jurnal Kependidikan, 2021)
The ability to understand math problems is needed to be able to solve it Mathematical problems, students' dislike of mathematics can causes high math anxiety which can affect understanding student math. This study aims to conduct a literature review on math anxiety and its effects. This study uses the SLR method (Systematic Literature Review). Data collection is done by documenting and reviewed all articles that had similar research in this research report. Article used in this study as many as 33 articles obtained from the google database scholar using the Publish or Perish application. Based on this research It was found that students' levels of math anxiety and anxiety were different mathematics has a negative effect on students' mathematics learning.Keywords: math anxiety, Effects of math anxiety, mathematics learning